Capture and return of sexual genomes by hybridogenetic frogs provide clonal genome enrichment in a sexual species - Doležálková-Kaštánková, Marie; Mazepa, Glib; Jeffries, Daniel L; Perrin, Nicolas; Plötner, Marcela; Plötner, Jörg; Guex, Gaston-Denis; Mikulíček, Peter; Poustka, Albert J; Grau, Jose; Choleva, Lukáš (Scientific reports, 2021)
Hybridogenesis is a reproductive tool for sexual parasitism. Hybridogenetic hybrids use gametes from their sexual host for their own reproduction, but sexual species gain no benefit from such matings as their genome is later eliminated. Here, we examine the presence of sexual parasitism in water frogs through crossing experiments and genome-wide data. We specifically focus on the famous Central-European populations where Pelophylax esculentus males (hybrids of P. ridibundus and P. lessonae) live with P. ridibundus. We identified a system where the hybrids commonly produce two types of clonal gametes (hybrid amphispermy). The haploid lessonae genome is clonally inherited from generation to generation and assures the maintenance of hybrids through a process, in which lessonae sperm fertilize P. ridibundus eggs. The haploid ridibundus genome in hybrids received from P. ridibundus a generation ago, is perpetuated as clonal ridibundus sperm and used to fertilize P. ridibundus eggs, yielding female P. ridibundus progeny. These results imply animal reproduction in which hybridogenetic taxa are not only sexual parasites, but also participate in the formation of a sexual taxon in a remarkable way. This occurs through a process by which sexual gametes are being captured, converted to clones, and returned to sexual populations in one generation.
Keywords: Microsatellite Repeats; analýza hlavních komponent; Rana ridibunda; mikrosatelitní repetice; Rana esculenta; Female; haploidie; Haploidy; genom; Animals; ženské pohlaví; mužské pohlaví; Genome; Male; Principal Component Analysis; zvířata; Genetic Loci; genetické lokusy